Engine performance and emissions using Jatropha curcas, Ceiba pentandra and Calophyllum inophyllum biodiesel in a CI diesel engine - Ong H.C.; Masjuki H.H.; Mahlia T.M.I.; Silitonga A.S.; Chong W.T.; Yusaf T. (Elsevier Ltd, 2023)
Biodiesel is a recognized replacement for diesel fuel in compressed ignition engines due to its significant environmental benefits. The purpose of this study is to investigate the engine performance and emissions produced from Jatropha curcas, Ceiba pentandra and Calophyllum inophyllum biodiesel in compressed ignition engine. The biodiesel production process and properties are discussed and a comparison of the three biodiesels as well as diesel fuel is undertaken. After that, engine performance and emissions testing was conducted using biodiesel blends 10%, 20%, 30% and 50% in a diesel engine at full throttle load. The engine performance shows that those biodiesel blends are suitable for use in diesel engines. A 10% biodiesel blend shows the best engine performance in terms of engine torque, engine power, fuel consumption and brake thermal efficiency among the all blending ratios for the three biodiesel blends. Biodiesel blends have also shown a significant reduction in CO2, CO and smoke opacity with a slight increase in NOx emissions. © 2014 Elsevier Ltd.